ANALISIS KELEMBAGAAN DAN PERANAN KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) DALAM PENGEMBANGAN WILAYAH KABUPATEN KERINCI - Mika Lestaria; Setia Hadi; M. Buce Saleh (Universitas Gadjah Mada, 2016)
Kerinci is one of regency with the large forest, but sub sector of forestry contributes only 0,04% of GDP Kerinci Regency. It’s may possibly by the weakness of forest management and policy of Kerinci Regency Government. Forest production management unit (KPHP) Model Kerinci establishment is one of goverment efforts to achieve sustainable forest management. Therefore, we need research with purpose: (1) to analyze the role of forest production management unit (KPHP) Model Kerinci in the regional development of Kerinci Regency; (2) to analyze the institutional of forest production management unit (KPHP) Model Kerinci; (3) to analyze region’s readiness forest production management unit (KPHP) Model Kerinci development. The study was conducted in Kerinci Regency. Data were analyzed by total economic value (TEV), institutional analysis, and analytical hierarchy process (AHP). The results showed that the total economic value of natural resources of KPHP Model Kerinci is Rp. 337.839.832.400 in a year, it’s mean that sub sector of forestry potentially to contribute about 8,38% of GDP Kerinci Regency. To realize the total economic values of natural resources of KPHP Model Kerinci, it needs strong institutions. Kerinci Regency is ready for KPHP Model Kerinci development, because it’s has the support from stakeholders.